Tantangan yang Harus Dihadapi Pimpinan Organisasi SI/TI di Indonesia Tahun 2014 - 2016 - Hudiarto Hudiarto (Universitas Multimedia Nusantara, 2013)
The job challenge of the leaders of the organization unit of IS / IT (CIO) has been shifted from the beginning as well as supporting routine tasks becomes more complex and varied that support decisionmaking at the levels of supervisors, middle managers and even top leaders. The problem is for years 2014-2016 and job description of IS/IT leaders have shifted towards a more strategic longer. Pervasive computing capability and versatility of use IS / IT ecofriendly has become a reasonable claim. So that why the organization unit of the IS / IT will be led by a CIO and must be assisted by the CTO, COO and CPO. Organizational units IS/IT is not something monolithic anymore but is a combination of four functions simultaneously, namely operating computerized systems, developing systems, designing architecture and is able to identify new business needs. Every function requires a certain membership groups and different management strategies. Oriented activities in support of strategic business more importantly needed by companies or government agencies. The method used in this research is the study of literature and interviews with respondents. The results of the research conducted is that the duties and functions in a variety of major government agencies appears to look uniform and can be interpreted broadly so that needs to be made more specific for the central leadership organization unit of IS/IT to answer the challenges of the future. While the CIO job description of some large-scale private enterprises is highly variable and depends on the ability of the top management and also the creativity of CIO. Considering year 2014 is no longer, then it should be the top management of private companies and government agencies begin to prepare. Index Terms - Chief Information Officer, IS/IT organizational management strategy, job challenge